Prenatal diagnosis of a 15q11.2-q14 deletion of paternal origin associated with increased nuchal translucency, mosaicism for de novo multiple unbalanced translocations involving 15q11-q14, 5qter, 15qter, 17pter and 3qter and Prader-Willi syndrome - Chih-Ping Chen; Ming-Huei Lin; Yi-Yung Chen; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Dai-Dyi Town; Meng-Shan Lee; Chen-Wen Pan; Wayseen Wang (Elsevier, 2021)
Objective: We present prenatal diagnosis of a 15q11.2-q14 deletion of paternal origin associated with increased nuchal translucency (NT), mosaicism for de novo multiple unbalanced translocations involving 15q11-q14, 5qter, 15qter, 17pter and 3qter, and Prader-Willi syndrome (PWS). Case report: A 32-year-old, primigravid woman underwent amniocentesis at 18 weeks of gestation because of an increased NT thickness of 5.6 mm and abnormal maternal serum screening results in the first trimester. The pregnancy was conceived by in vitro fertilization and embryo transfer. Amniocentesis revealed a karyotype of 45,XX,der(5)t(5;15)(q35;q14),-15 [16]/45,XX,-15,der(17)t(15;17)(q14;p13)[3]/45,XX,der(15)t(15;15)(q35;q14),-15[2]. The parental karyotypes were normal. Prenatal ultrasound findings were unremarkable. Array comparative genomic hybridization (aCGH) analysis on the DNA extracted from cultured amniocytes revealed the result of arr 15q11.2q14 (22,765,628-38,651,755) × 1.0 [GRCh37 (hg19)] with a 15.886-Mb 15q11.2-q14 deletion encompassing TUBGCP5, CYFIP1, NIPA2, NIPA1, SNRPN, SNURF, SNORD116-1, IPW, UBE3A, ACTC1 and MEIS2. The pregnancy was subsequently terminated, and a malformed fetus with facial dysmorphism was delivered. The cord blood had a karyotype of 45,XX,der(5)t(5;15)(q35;q14),-15[46]/45,XX,der(3)t(3;15) (q29;q14),-15[2]/45,XX,-15,der(17)t(15;17)(q14;p13)[2]. The placenta had a karyotype of 45,XX,der(5) t(5;15)(q35;q14),-15. Polymorphic DNA marker analysis confirmed a paternal origin of the proximal 15q deletion. Conclusion: Increased NT and abnormal maternal serum screening results may prenatally be associated with PWS. Chromosome 15 rearrangements in PWS include mosaicism for de novo multiple unbalanced translocations.